A People’s Writer for Peasant Readers: The Early Reception of Žemaitė’s Writings (1895–1915) - Bleizgienė, Ramunė (Literatūra, 2019)
This article investigates the rise of the peasantry as new readers and Lithuanian intellectuals’ reactions to this phenomenon as they took the initiative in directing the peasants’ cultivation as readers. These intellectuals were concerned with the development of the peasants and sought to form their reading habits, influence the readers’ choices as to reading material, and so on. This article goes on to analyze how Žemaitė’s status as a peasant writer was established during her early reception, and how the evaluation of her work depended on the imagined addressee. By analyzing the reviews and broader studies of Žemaitė’s published works in the Lithuanian press from 1895 to 1915, this article aims to show that the formation of the common people as a potential and especially important national reading public was an integral part of her canonization process. Yet another important aim of this research is to reveal how the reception of Žemaitė’s works brought ordinary village peasant onto the horizon of modern Lithuanian culture, and how this became the foundation of one of the new literary styles in Lithuania, namely realism. In this way, by canonizing Žemaitė’s works, the life of village folk became not only visible and recognizable to the Lithuanian reading public, but also came to be regarded as a credible topic for realistic prose.
Keywords: Žemaitė; reception; peasants; new readership; realism